PTH-171 Colonoscopy Performance in Extended Three Session Working Days. (4th June 2013) - Subramanian, S; Haslam, N; Collins, P; Sarkar, S
Abstract : Introduction: Three session working days were introduced in our endoscopy unit to accommodate the increasing demand for endoscopic procedures. There is evidence to suggest that caecal intubation rate (CIR) and polyp detection rate (PDR) declines as the day progresses in a standard two session working day. There is currently no literature on CIR and PDR for an extended 3-session working day. The aim of this study was to characterise the impact of endoscopist fatigue on quality of colonoscopy performance by comparing outcomes based on time of day and chronological procedure order for an extended working day. Methods: We conducted a retrospective audit of all colonoscopies undertaken in our unit between January and December 2011. In order to assess the effect of repetitive fatigue, endoscopy lists with < 3 colonoscopies were excluded. Time of colonoscopy was stratified into three categories by the starting time of the scheduled list – morning (AM), afternoon (PM), and evening (PM). Queue position was defined as the order that the colonoscopy was performed on the same list i.e. 1st, 2nd and so on. Data on potential confounders including age, sex, quality of bowel preparation (recorded on a three point rating scale of good, satisfactory and poor) were recorded. To evaluate the effect of endoscopist fatigue on colonoscopy performance, we analysed CIR and PDR according to time of day and queue position. Results: A total of 2520 colonoscopies were included, of which 1299 (51.5%) were male and 1221 (48.5%) female. The median age was 63 (interquartile range, IQR, 51–70). 1062 (42.2%) were performed in AM lists, 984 PM (39.1%) and 470 EVE (18.7%). CIR did not vary according to time of day (89.8, 90 and 89.5% for AM, PM and EVE lists respectively, p = NS). In multivariate analysis, CIR was adversely affected by age > 70, female gender, poor bowel preparation (all p < 0.01) but not queue position. PDR was not influenced by time of day or queue position. PDR was higher in men in multivariate analyses (p < 0.01). Conclusion: Colonoscopy quality is not dependent on time of day or queue position in an extended 3 session day. Our findings support the provision of 3 session days to meet the increasing demand for colonoscopy. Disclosure of Interest: S. Subramanian Speaker bureau with: Shire, Dr Falk, Abbott, Conflict with: Advisory board for Abbott, Vifor Pharma, N. Haslam: None Declared, P. Collins: None Declared, S. Sarkar: None Declared